Effect of company profitability, size, and growth on corporate social responsibility disclosure in food and beverage sector companies - Endang Mardiati; Laila Fitriyah; Lutfia Nurlaili (Enrichment : Journal of Management, 2023)
Environmental pollution that occurs due to company activities, one of which is a food and beverage sector companies. This relates to the high level of production that will produce industrial waste to the company and the environment. Besides the environmental pollution carried out, of course every company needs to focus on CSR programs in accordance with the activities of their respective companies, in order to restore balance in the surrounding environment. Based on these conditions, further this research aims to examine the effect of profitability, size, and company growth on CSR disclosure. The population and sample in this study were 60 data from sector companiesfood and beverage registered on the Indonesia Stock Exchange in 2014-2017. This research uses purposive sampling method and secondary data. The analysis technique used is multiple regression analysis. The results of this study indicate that corporate profitability is one of the factors that can influence CSR disclosure. The higher the profitability of the company, the greater the disclosure of CSR made. Meanwhile, the size and growth of the company has no effect on CSR disclosure. This means that the size of the company is not a benchmark in expressing CSR, while company growth can be seen from the behavior of consumers who have not paid attention to companies that do CSR in choosing a product.